Overview of nature-based solutions for climate resilience in the MENA region - Karen Gebrael; George Mitri; Olga-Ioanna Kalantzi (Nature-Based Solutions)
Climate change is increasing rapidly and the world will be subjected to additional severe weather events and natural disasters, therefore immediate actions are needed to mitigate and adapt climate change. Nature-based solutions (NBS) are recognized globally among the most effective strategies to address climate change. The Middle East and North Africa (MENA) region is one of the most affected regions by climate change; however, there is still limited knowledge about NBS implementation in this area. This study aims to explore the adoption and scope of NBS initiatives within the MENA region, providing a broad overview of the current situation. The specific objectives are to: 1) undertake a comprehensive literature review and database examination to assist decision-makers in recognizing NBS strategies pertinent to the MENA region, addressing the notable scarcity of reviews on NBS in this area; 2) classify the identified NBS strategies based on ecosystem types, challenges related to climate change, the economic status of countries, and types of interventions; and 3) identify and discuss the primary gaps in the implementation of NBS strategies in the MENA region, with the intent of fostering further research and enhancing the development and application of NBS strategies. Our findings indicate that the majority of identified case studies report on ecosystem-based disaster risk reduction measures targeting land degradation, drought, food insecurity, and water scarcity, implemented primarily in terrestrial forests/woodlands and agricultural lands. This study contributes to improving the understanding of NBS implementation in MENA countries, thereby assisting policymakers and governments in enhancing NBS strategies.